Impact of Echocardiographic Parameters on Recurrent Stroke in the Randomized REDUCE PFO Cryptogenic Stroke Trial. Issue 4 (4th July 2021) - Lefebvre, Bénédicte; Naidu, Suveeksha; Nathan, Ashwin S.; Chen, Zhen; Ky, Bonnie; Silvestry, Frank E.; Søndergaard, Lars; Settergren, Magnus; Nielsen-Kudsk, Jens Erik; Rhodes, John F.; Kasner, Scott E.; Herrmann, Howard C.
ABSTRACT: Background: Transcatheter closure of patent foramen ovale (PFO) in cryptogenic stroke reduces the risk for recurrent stroke, but whether anatomic parameters can predict this remains unclear. We examined the associations between quantitated transesophageal echocardiogram (TEE) parameters and recurrent stroke in a large randomized study of PFO closure with adjudicated endpoints. Methods: Baseline TEEs from the REDUCE trial comparing medically treated patients with transcatheter closure were analyzed by a trained sonographer blinded to patient characteristics. Associations between echocardiographic parameters with recurrent stroke and treatment groups were determined with a log-rank test and Cox multivariable regression. Results: All TEEs were analyzed (180 medically treated, 358 PFO closure; mean age 45 years). Parameters were similar, including large shunt (22%), hypermobile septum (27%), eustachian valve (26%), and Chiari network (7%). Atrial septum aneurysm (ASA) was observed more frequently in the medically treated group (12% vs 6%, p = 0.018). Among patients in the medically treated group, there was a signal toward higher incidence of recurrent stroke to 5 years with than without ASA (19% vs 6%, p = 0.097), for large shunt (15% vs 5%, p = 0.116), and was significantly higher for ASA or hypermobile septum with large shunt (67% vs 5%, p ≤ 0.001 and 29% vs 6%, p = 0.036, respectively). Closure was associated with a lower risk of stroke in all subgroups. Conclusions: In this TEE analysis of cryptogenic stroke patients, recurrent stroke was higher in medically treated patients with ASA or hypermobile septum and a large shunt. The relative reduction of stroke with transcatheter PFO closure was similar regardless of anatomy, suggesting that treatment should not be limited to these patients. Abbreviations: ASA, atrial septum aneurysm; CI, confidence interval; EV, eustachian valve; IQR, interquartile range; KM, Kaplan–Meier; LA, left atrium; PFO, patent foramen ovale; RA, right atrium; SD, standard deviation; TEE, transesophageal echocardiogram.